EFEKTIVITAS STRATEGI-KOMUNIKASI SATGAS COVID-19 RI DALAM MENGIMBAU MASYARAKAT UNTUK MELAKUKAN VAKSIN - Ramadhan, Febriansyah (Interaksi: Jurnal Ilmu Komunikasi, 2023)
This study aims to determine the effectiveness of communication strategy used by the Ministry of Health of The Republic of Indonesia, especially the COVID-19 Task Force in overcoming the spread of the virus by conducting a vaccination program for the community. The spreading of COVID-19 still requires special treatment in various countries, including Indonesia. Besides implementing health protocols, the government must take concrete preventive steps in overcoming this pandemic, namely by providing vaccines for the community. Even though the vaccination program is an effort to prevent the spread of COVID-19, there are still people who refuse to vaccinate or do not know the importance of this vaccination. The use of public relations programs using information technology in the form of the internet is urgently needed during this pandemic. One of the media used by the government is a website which is also supported through social media. Using qualitative reasearch approach case study method, this research analyzed information content related to the government's vaccination program on the covid19.go.id website. Based on the results of information categorization and analysis of information content published on the covid19.go.id website, it can be concluded that the communication strategy by the COVID-19 Task Force public relations is quite effective because information about the implementation of COVID-19 vaccination and the availability of vaccines in Indonesia is continuously updated.